Peningkatan Pengetahuan Pengelolaan Keuangan Pada RT 02 RW 11 Kelurahan Ciputat Tangerang Selatan - Lisa Amru; Erni Hernawati; Anita Anita (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Financial management is an important aspect of a community organization. Good and accurate financial management will help a community organization to understand the financial situation within the organization. The implementation of Community Service aims to provide socialization to enhance financial management knowledge among the RT 02 RW 11 administrators in Ciputat, South Tangerang. Neighbourhood 02 Neighbourhood Head 11 in the Ciputat subdistrict oversees 588 family heads (KK) within its administration and manages its finances independently without specific regulations from the government. The absence of established regulations makes the RT administrators less understanding of how to record and manage finances using good accounting methods. The method used in this community service is socialization regarding financial management in organizations. The result of this service is that Neighborhood Association 02 understands how to manage finances properly according to accounting methods.